Innate immune receptor NOD2 promotes vascular inflammation and formation of lipid‐rich necrotic cores in hypercholesterolemic mice. Issue 10 (25th August 2014) - Johansson, Maria E.; Zhang, Xiao‐Ying; Edfeldt, Kristina; Lundberg, Anna M.; Levin, Malin C.; Borén, Jan; Li, Wei; Yuan, Xi‐Ming; Folkersen, Lasse; Eriksson, Per; Hedin, Ulf; Low, Hann; et al.
<x xml:space="preserve">Abstract</x> Atherosclerosis is an inflammatory disease associated with the activation of innate immune TLRs and nucleotide‐binding oligomerization domain‐containing protein (NOD)‐like receptor pathways. However, the function of most innate immune receptors in atherosclerosis remains unclear. Here, we show that NOD2 is a crucial innate immune receptor influencing vascular inflammation and atherosclerosis severity. 10‐week stimulation with muramyl dipeptide (MDP), the NOD2 cognate ligand, aggravated atherosclerosis, as indicated by the augmented lesion burden, increased vascular inflammation and enlarged lipid‐rich necrotic cores in Ldlr−/− mice. Myeloid‐specific ablation of NOD2, but not its downstream kinase, receptor‐interacting serine/threonine‐protein kinase 2, restrained the expansion of the lipid‐rich necrotic core in Ldlr−/− chimeric mice. In vitro stimulation of macrophages with MDP enhanced the uptake of oxidized low‐density lipoprotein and impaired cholesterol efflux in concordance with upregulation of scavenger receptor A1/2 and downregulation of ATP‐binding cassette transporter A1. Ex vivo stimulation of human carotid plaques with MDP led to increased activation of inflammatory signaling pathways p38 MAPK and NF‐κB‐mediated release of proinflammatory cytokines. Altogether, this study suggests that NOD2 contributes to the expansion of the lipid‐rich necrotic core and promotes vascular inflammation in atherosclerosis.